2021
DOI: 10.1038/s41598-021-97564-1
|View full text |Cite
|
Sign up to set email alerts
|

Nadir CA-125 has prognostic value for recurrence, but not for survival in patients with ovarian cancer

Abstract: The objective of this study was to evaluate the nadir CA-125 in patients with epithelial ovarian cancer. A total of 168 patients who achieved complete remission (no clinical and radiological signs, CA-125 ≤ 35 U/ml) after first-line treatment were enrolled in the study. The relationship between CA-125 and survival was examined by applying generalized additive models to the Cox proportional hazards model. The median CA-125 concentration after the treatment was 10 U/ml (2.7–35 U/ml). The nadir CA-125 was related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…However, we found a significant association of post-treatment CA-125 levels with the risk of progression and death in this cohort. Previous studies have shown that the nadir of CA-125 levels are associated with PFS and OS in high-grade serous ovarian cancer [24,25]. In the MVA, after controlling for age and FIGO stage, an elevated post-treatment CA-125 level remained an independent risk factor for disease progression and death.…”
Section: Discussionmentioning
confidence: 77%
“…However, we found a significant association of post-treatment CA-125 levels with the risk of progression and death in this cohort. Previous studies have shown that the nadir of CA-125 levels are associated with PFS and OS in high-grade serous ovarian cancer [24,25]. In the MVA, after controlling for age and FIGO stage, an elevated post-treatment CA-125 level remained an independent risk factor for disease progression and death.…”
Section: Discussionmentioning
confidence: 77%
“…However, elevated preoperative CA 125 (>249.5 U/mL) was significantly associated with short OS. The study by Piatek et al, (2021) lightened the prognostic role of CA 125 level in recurrence rate but didn't show a significant relationship with OS.…”
Section: Discussionmentioning
confidence: 90%
“…Our study confirmed the very strong prognostic value of CA-125 nadir concentration below the threshold (<35 IU/L) [HR = 0.23 and 0.35 in the uni- and multi-variate analyses, respectively, versus HR = 0.46 in previous studies ( 44 , 45 )]. Another study found that CA-125 nadir concentration after first-line treatment was associated with PFS, but not with overall survival ( 46 ).…”
Section: Discussionmentioning
confidence: 99%